2005
DOI: 10.1111/j.1600-0838.2005.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily physical activity in Swedish children aged 8–11 years

Abstract: Introduction: Physical inactivity is hypothesized to be a contributing factor in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
72
1
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 25 publications
8
72
1
10
Order By: Relevance
“…However, only 4 of these articles [13][14][15][16] were included in this report card since the other 39 articles did not provide any estimates of the percentage of children and adolescents meeting the PA recommendations. In total, 4 studies objectively measured MVPA [13][14][15][16] and 1 subjectively measured SB (screen time; ie, TV/DVD/video viewing) 13 in relation to the recommendations. The amount of children reaching the recommendation for overall PA was assessed via those who fulfilled the recommendations of greater than 60 minutes of MVPA in accordance with the NNR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only 4 of these articles [13][14][15][16] were included in this report card since the other 39 articles did not provide any estimates of the percentage of children and adolescents meeting the PA recommendations. In total, 4 studies objectively measured MVPA [13][14][15][16] and 1 subjectively measured SB (screen time; ie, TV/DVD/video viewing) 13 in relation to the recommendations. The amount of children reaching the recommendation for overall PA was assessed via those who fulfilled the recommendations of greater than 60 minutes of MVPA in accordance with the NNR.…”
Section: Methodsmentioning
confidence: 99%
“…13 Three older reports in this age group used lower cut-points for MVPA and reported that as many as 93% to 100% of 8-to 11-year-old children (boys and girls) fulfilled the recommendation. [14][15][16] For adolescents, 10% and 15% of 13-and 15-year-olds reached the allotted 60 minutes. 23 …”
Section: Variables and Their Contribution To Pa Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…La clasificación de los sujetos de la muestra, conforme a la propuesta realizada en el Manual de Cineatropometría 38 de la Federación Española de Medicina Deportiva, se resume en la tabla 2. Sin embargo, hemos de señalar que los resultados expuestos pueden contener un cierto sesgo debido a que no incluyen a las 10 mujeres con un sobrepeso evidente que no pudieron incluirse en el estudio por negarse a ser medidas y/o pesadas.…”
Section: Nivel De Adiposidad Corporalunclassified
“…Al igual que en la gran mayoría de estudios revisados, encontramos diferencias muy claras en el NAF en ambos sexos 2,9,10,29,36,[38][39][40][41][42][43][44] . Sin embargo, nuestros resultados entre las mujeres no son tan dramáticos como los encontrados entre las mujeres italianas de 14 a 18 años donde encontraron un 8% de mujeres activas y un 65% de inactivas o sedentarias 12 .…”
Section: Figuraunclassified